The Impact of Hospital Closures on Medical Debt in Collections: Analysis Using Consumer Credit Bureau Data - Jennifer Andre; Fredric Blavin; Breno Braga; Anuj Gangopadhyaya (Institute of Labor Economics (IZA), 2023)
This study presents new evidence on the potential detrimental effects of hospital closures. We examine how hospital closures affect the likelihood of incurring medical debt. Hospital closures can increase market concentration by removing a competitor from the market. Closures can also have negative spillover effects on the local economy and affect the population's ability to pay their bills. We combine 2011-2020 consumer credit bureau data with information on hospital closures from 2014-2018 to assess the relationship between closures and medical debt. Using a stacked event study approach, we find that a closure that reduces hospital supply in a Hospital Referral Region (HRR) by 10 percent is associated with a 4 percent increase in the share of consumers with medical debt, with larger effects in HRRs that are urban and have higher rates of poverty. Moreover, we find that a hospital closure is associated with about a 6-8 percent increase in hospital market concentration. These findings suggest that the primary mechanism through which hospital closures affect medical debt is by reducing hospital competition in local markets.
Keywords: I11; I14; I18; 330; medical debt; hospital closures; hospital competition